쇼케이스의 현장 데이터 측정 및 분석 - 신유환; 오왕규; 박기호; 김영일; 신영기 (대한설비공학회, 2005)
Experimental study was performed to understand the operation of an on-site showcase working in a super discount store. Inlet and outlet temperatures of evaporator, condenser, expansion valve and compressor were measured for both air and refrigerant sides. Electric power consumption of compressors, defrosting heaters, cooling water pumps and etc. were measured. The operating characteristics of the showcase system under various working conditions were analyzed and discussed. During the defrosting process, the air temperature inside the showcase increased to 15℃, which gave harmful effect to the frozen food. The collected data will serve as valuable information for diagnosing and improving the performance of showcases.